(3GdeNJGQ ef cJGH GdaGThT aj CMcGe bQGbhTs - (3eLghds; (3CSYO Hf egqPH Hf ejfG Hf RcQjG, GHf eeGJj , CHh GdecGQe,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYbd CTQa GdCSHGH bGd GdSYjO Hf eeGJi Efffi deG QCjJ Ybd HgGA GdOjf bQGbhT eNQeI aGThT aUfaJ gPG GdcJGH s
(3BNQgG (B:s
(3Je GdeNJGQ ef cJGH GdaGThT hddg GdMeO hGdefI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B169 - (3U(B173s
(3jdjgG fbhd eNJdaI ef cJH eNJdaI ef hQbI (B174-197s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs